'Come together?' Citizens and civil servants dialogue and trust. Issue 2 (29th April 2019) - Güemes, Cecilia; Resina, Jorge
Abstract: Trust is a key element in the co‐creation of solution for public problems. Working together is a gradual learning exercise that helps to shape emotions and attitudes and to create the foundations of trust. However, little is known about how institutions can promote trust. With the intention of going deeper into the subject, this paper focuses on a local experience in Spain: Madrid Escucha, a City Council initiative aimed at stimulating dialogue between officials and citizens around projects to improve city life. Three are our questions: who participate in these spaces, how the interactions are, and what advances are achieved. Based on qualitative research, empirical findings confirm a biased participation in this kind of scenarios as well as the presence of prejudices on both sides, an interaction characterised by initial idealism followed by discouragement and a possible readjustment, and a final satisfaction with the process even when results are not successful. Abstract : This article provides empirical findings about institutional initiatives aimed to promote dialogue and trust between official and citizens in the co‐creation of solutions of public problems. Based on qualitative research, we analyze a local program in Spain and conclude that in spite of prejudices, participants get a final satisfaction.